Basketball lay-up - foot loading characteristics and the number of trials necessary to obtain stable plantar pressure variables - Chua, Y. H. K.; Quek, R. K. K.; Kong, P. W. (Sports Biomechanics, 2017)
This study aimed (1) to profile the plantar loading characteristics when performing the basketball lay-up in a realistic setting and (2) to determine the number of trials necessary to establish a stable mean for plantar loading variables during the lay-up. Thirteen university male basketball players [age: 23.0 (1.4) years, height: 1.75 (0.05) m, mass: 68.4 (8.6) kg] performed ten successful basketball lay-ups from a stationary position. Plantar loading variables were recorded using the Novel Pedar-X in-shoe system. Loading variables including peak force, peak pressure, and pressure-time integral were extracted from eight foot regions. Performance stability of plantar loading variables during the take-off and landing steps were assessed using the sequential averaging technique and intra-class correlation coefficient (ICC). High plantar loadings were experienced at the heel during the take-off steps, and both the heel and forefoot regions upon landing. The sequential estimation technique revealed a five-eight trial range to achieve a stable mean across all plantar loading variables, whereas ICC analysis was insensitive to inter-trial differences of repeated lay-up performances. Future studies and performance evaluation protocols on plantar loading during basketball lay-ups should include at least eight trials to ensure that the measurements obtained are sufficiently stable. ABSTRACT FROM AUTHOR